Breastfeeding Practices among New Mothers in the Postnatal Ward of District Hospital, Ujjain, Madhya Pradesh: A Knowledge, Attitude, and Practice Study - Roshni Ganguly (International Journal of Nursing Research, 2024)
Aims: This study compares 1st-time mothers with those who have previously given birth, examines factors that affect infant feeding practices, and evaluates the knowledge, attitudes, and practices (KAP) regarding breastfeeding among new mothers in the postnatal ward of a district hospital in Ujjain, Madhya Pradesh. Introduction: Breastfeeding is vital for the health of infants because it supports their immune systems and provides necessary nutrients. Because of varying degrees of knowledge, attitudes, and sociocultural influences, breastfeeding behaviors vary despite its well-established advantages. Understanding these characteristics is critical for developing tailored interventions that support good breastfeeding. Materials and Methods: This mixed-method, cross-sectional study was carried out in the Ujjain District Hospital’s postnatal ward. Convenience sampling was used to collect data from new mothers who completed a standardized questionnaire. The KAP of breastfeeding was investigated in the study, with a focus on contrasting the answers of 1st-time mothers with those of women who had previously given birth. Results: The study’s findings showed that while the majority of moms knew the advantages of breastfeeding, they lacked thorough understanding of exclusive breastfeeding techniques. Practices differed, with some mothers unable to start breastfeeding within the 1st h after giving birth or to maintain breastfeeding exclusively for 6 months, despite generally positive attitudes. Compared to moms who had previously given birth, 1st-time mothers had a higher need for assistance and direction. Conclusion: According to the survey, new moms in Ujjain have serious gaps in their knowledge and habits about nursing. To increase breastfeeding behaviors and results, more healthcare practitioners should give instruction and support.